If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-n-4(4n-1)=72
We move all terms to the left:
-n-4(4n-1)-(72)=0
We add all the numbers together, and all the variables
-1n-4(4n-1)-72=0
We multiply parentheses
-1n-16n+4-72=0
We add all the numbers together, and all the variables
-17n-68=0
We move all terms containing n to the left, all other terms to the right
-17n=68
n=68/-17
n=-4
| 18x+26=8 | | 225=84-x | | (4x+16)=(5x-12) | | 229=127-v | | 2-s=4 | | X+13=4x-20 | | −20+14m=10m+16 | | 9(-2x+11)=-207 | | x+6.8=12.9 | | 17x+5=-1x+18 | | 54-y=229 | | 14=2t+2 | | 212-v=290 | | 187=70-w | | 5(-4x+14)=-190 | | 12÷x-3=30÷x | | 5c+-9c-9c+6=-20 | | 2.5d+6.75= | | 7x-9=1/2(46-2x) | | -m/6=7 | | 3(-7x+7)=-63 | | 12÷x-3=30/x | | 4(r-14)+6=18 | | 8x+25=2x-29 | | 8x=4-3x=24 | | 0=16x^2-4x | | 7(9x+6)=609 | | 3u+15=60 | | 4(2x+1)=27+3(2x−5)= | | 0=16n^2-4n | | 234=12-u | | 7(-4x+17)=-413 |